Effectiveness of Management Information Systems in Elementary Schools: A Systematic Literature Review - Freddy Wicaksono; Ketut Widhi Adnyana; Fahmi; Yudi Wahyudin; Bagja Nugraha; Enjang Yusup Ali (Indonesian Journal of Educational Research and Review, 2026)
The effectiveness of Management Information Systems (MIS) in elementary schools has become an important issue as educational governance increasingly requires efficient, accurate, transparent, and data-based management. This study aims to systematically examine the effectiveness of MIS implementation in elementary schools and identify its supporting factors, barriers, and implications for educational service quality. A Systematic Literature Review (SLR) method was employed by following the PRISMA stages, including identification, screening, eligibility assessment, and article inclusion. A total of 22 scientific articles published between 2020 and 2025 were analyzed thematically based on implementation focus, effectiveness, supporting factors, barriers, and the impacts of MIS. The findings show that MIS plays a positive role in improving administrative efficiency, data management accuracy, reporting transparency, internal school coordination, and communication between schools and parents. This system also helps schools strengthen decision-making through faster, more organized, and better documented information. The main supporting factors include technological infrastructure, teachers’ and administrative staff’s digital competence, principal leadership, and policy support. Persistent barriers include limited internet access, inadequate hardware, user resistance, and insufficient technical assistance. These findings confirm that MIS is effective in strengthening elementary school governance and educational service quality, although empirical evidence regarding its direct impact on student learning outcomes remains limited and requires further investigation.